Heterogeneity and main controlling factors of black shale in first Member of Lower Carboniferous Luzhai Formation in Northern Liucheng Slope, Guizhong Depression - LIN Yifei; QIN Yinglun; LU Yongchao; ZHUO Seqiang; WANG Chuan; LU Wenshi; CUI Qinyu; CEN Wenpan (Youqi dizhi yu caishoulu)
The black shale of the Lower Carboniferous Luzhai Formation in the Northern Liucheng Slope of the Guizhong Depression has strong vertical heterogeneity， which seriously restricts the evaluation and fracturing ability of the shale reservoir in the later stage. The isochronal stratigraphic sequence framework of the study area was established based on data from logging， cores， thin section observation， organic carbon test， X-ray diffraction mineralogy measurement， and XRF element scanning. Within the stratigraphic sequence framework， the heterogeneity of the reservoir was studied， and the main factors controlling the heterogeneity were discussed according to the recovered paleoenvironmental information. The results show that three third-order sequences can be identified in the first Member of the Luzhai Formation， and seven quasi-sequences （i.e.， seven layers） can be identified in the first Submember of the first Member of the Luzhai Formation. The distribution of organic carbon content， mineral composition content， and shale lithofacies has strong vertical heterogeneity， and different layers exhibit obvious differences. The high organic carbon content is mainly concentrated in the middle and upper part of layer ① and the bottom of layer ③. Mud-rich siliceous， mixed， and silica-rich calcareous shale lithofacies are mainly developed in the study area. According to the organic carbon content， the mud-rich siliceous shale lithofacies is considered to be the high-quality lithofacies in the study area， which is mainly concentrated in the bottom of layer ③. The heterogeneity of the shale in the first Submember of the first Member of Luzhai Formation is controlled by paleoproductivity， redox conditions， and terrestrial input. High paleoproductivity and the anoxic sedimentary environment are conducive to the accumulation and preservation of organic matter in the middle stage of layer ① and the early stage of layer ③. An appropriate amount of terrestrial input can carry the appropriate amount of nutrients and increase the abundance of organic matter， ensuring the development of mud-rich siliceous shale with abundant organic carbon.